INTERNAL AND EXTERNAL AUDITS ISO 9001:2015: A CRITICAL ANALYSIS ON COMPLIANCE AND STRATEGIC VALUE - Medeiro, Juliana (Revista Gênero e Interdisciplinaridade, 2025)
This article presents an in-depth analysis of the role of quality management system (QMS) audits under the ISO 9001:2015 standard, investigating how these transcend the function of compliance verification to become a pillar of strategic value and corporate governance. The research, theoretical in nature and based on a systematic literature review, explores the dichotomy and synergy between internal and external audits, contextualizing them within the PDCA cycle and risk-based thinking. It analyzes the effectiveness of audits as drivers of continuous improvement and their impact on organizational performance, based on empirical evidence. Additionally, the study correlates the maturity of ISO 9001 certification with business excellence models, such as EFQM. The discussion delves into the auditor’s competence as a critical factor and the alignment of audit programs with top management, proposing that audit results be used as business intelligence. It is concluded that the effective integration of audits into business strategy is a competitive differential, transforming a normative requirement into a driver of resilience and sustainable excellence.